Undergraduate students' and interns' perception towards learning environment at dental clinics, Qassim University, Saudi Arabia - Muhammad Qasim Javed; Shazia Nawabi; Swati Srivastava; Shahul H Kolarkodi; Asma M Khan; Minal V Awinashe (Wolters Kluwer Medknow Publications, 2023)
Background: Dental clinical educational environment plays a critical part in the inculcation of skills and enhancement of knowledge for the dental students. The objective was to assess undergraduate dental students' and interns' perceptions towards the clinical learning environment. Methods: Current cross-sectional study was conducted from December 2020 to February 2021, using the 24-item dental clinical learning environment inventory (DECLEI) on a six point Likert scale. The possible range of cumulative score for DECLEI was from 0 to 100 (interpretation poor to excellent). The inventory was emailed to 111 students and interns at College of Dentistry, Qassim University. The relationship between the independent variables and DECLEI scores was determined by using Pearson correlation test. SPSS version-23 was used for statistical analysis. Results: Overall response rate was 78.37%. The mean DECLEI score was noted as 67.5 ± 17.98. Among the factors, the highest mean score was documented for the systematic self-evaluation and the lowest mean score was observed for the item related to patients' punctuality for appointments. A factor-wise analysis of three subscales of DECLEI demonstrated the respondents had good perception towards all subscales with the highest mean score (72.3 ± 18.06) for Factor III and lowest mean score (61.3 ± 19.81) for Factor II. Overall, the DECELI was found to be reliable with the Cronbach's Alpha value of 0.94. The Pearson's correlation test showed the weak positive insignificant correlation of mean DECLEI score with gender and categories.Conclusions: Present study indicated more positive than negative perceptions of the dental students related to their clinical learning environment. The DECLEI helped in recognizing both strengths and shortcomings of the dental clinical learning environment.